2016
DOI: 10.3945/jn.115.214098
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Milk-Fat-Globule Membrane Affects Resistance to Diarrheagenic Escherichia coli in Healthy Adults in a Randomized, Placebo-Controlled, Double-Blind Study

Abstract: The attenuated diarrheagenic E. coli strain transiently induced mild symptoms of a food-borne infection, with complete recovery of reported clinical symptoms within 2 d. The present diarrheagenic E. coli challenge trial conducted in healthy adults indicates that a milk concentrate rich in natural, bioactive phospho- and sphingolipids from the MFGM may improve in vivo resistance to diarrheagenic E. coli. This trial was registered at clinicaltrials.gov as NCT01800396.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 35 publications
7
43
0
Order By: Relevance
“…Novakovic et al found that the isolated individual proteins of porcine MFGM could inhibit F4ac‐positive enterotoxigenic E. coli from attaching to host intestinal epithelium . E.coli challenge studies in healthy adults also demonstrated protective effects of MFGM . Our findings are consistent with these studies, and the antimicrobial constituents of MFGM also contributed to the overall improvement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Novakovic et al found that the isolated individual proteins of porcine MFGM could inhibit F4ac‐positive enterotoxigenic E. coli from attaching to host intestinal epithelium . E.coli challenge studies in healthy adults also demonstrated protective effects of MFGM . Our findings are consistent with these studies, and the antimicrobial constituents of MFGM also contributed to the overall improvement.…”
Section: Discussionsupporting
confidence: 90%
“…From day 2 to day 14 postoperation, both Sham and SBS groups received daily administration of 1mL double-distilled (dd) water by intragastric gavage, while the SBS+MFGM group was gavaged with MFGM (Lacprodan MFGM-10, Arla Foods Ingredients group, Aarhus, Denmark) resolved in 1 mL dd water at a dosage of 1.5g/kg/d. [19][20][21] Body weight and food intake were monitored every day. Stool consistency was recorded and rated on a defined scale where 0 = formed pellets, 2 = loose or semiformed, 4 = watery.…”
Section: Experimental Designmentioning
confidence: 99%
“…These results are not unexpected as previous authors found that MFGM from raw or heat-treated milk inhibited the expression of the Shiga toxin gene in E. coli O157:H7 [25] while in humans orally challenged with live, attenuated diarrheagenic E. coli the intake of a milk protein concentrate rich in MFGM improved the in vivo resistance to this bacteria [26]. …”
Section: Introductionsupporting
confidence: 58%
“…We recently reported that infants fed the MFGM supplemented formula had a lower incidence of AOM and less use of antipyretics [17], and Bruggencate et al [34] found that MFGM intake reduced Escherichia coli induced diarrhea in adults. Taken together, these results support a modifying effect of MFGM on the proliferation of certain bacterial species and/or symptoms of infection.…”
Section: Discussionmentioning
confidence: 99%